The Phenomenological Analysis of the Impact of Digital Overstimulation on Attention Control in Elementary School Students: A Study on the 'Brain Rot' Phenomenon in the Learning Process - Eogenie Lakilaki; Roza Melinda Puri; Angga Nuraufa Zamzami Saputra; Ayu Nur Shawmi; Nur Asiah; Muhammad Rizky (The Future of Education Journal, 2025)
This study examines the impact of digital overstimulation on attention control in elementary school students, particularly concerning the phenomenon of "brain rot" in the learning process. Using a phenomenological approach, this research explores the subjective experiences of students in dealing with the challenges of attention control in the digital age. Data was collected through in-depth interviews with students and teachers, as well as direct observations in the learning environment, and was further supported by various literatures. The findings reveal that excessive exposure to digital media contributes to a decline in focus ability, particularly in tasks that require sustained attention. Students experience difficulty transitioning from digital activities to conventional learning and exhibit signs of disorientation and stress when faced with tasks requiring continuous focus. The study also highlights the important role of teachers and parents in moderating the use of digital media and developing effective attention control strategies. Simple restorative interventions, such as outdoor break times and focus rehabilitation techniques, have been shown to help reduce attention fatigue complaints among students.